Collaborative Governance in the Development of Sowan Beach Tourism in Bancar District - Anggita Putri Fatmawati (PERSPEKTIF, 2023)
This article aims to find out how the forms of coastal tourism development are Sowan Beach, Bancar-Tuban District, East Java. The focus of the problem from this research is that in the process of developing Sowan beach tourism carried out by Perhutani Jatirogo with the village community around the tour, it is not in accordance with what is expected. In order to analyze this problem, the author uses the reference theory from Ansell and Gash and Agranoff and Mc. Guire. The data in this study were collected using interview techniques through informants and supported by a literature study for interview data, and in this study were analyzed qualitatively. In this study, it can be concluded that the collaborative governance process that occurred at Sowan Beach took place unequally with the Abstinence model. It was emphasized that the Perhutani party did not involve and pay attention to the Bogorejo Village community regarding tourism development. This is supported by the empirical fact that in making decisions on tourism development on Sowan Beach it is only carried out by the Jatirogo forestry party without involving the Bogorejo village community. The aspirations of the community for the development of the Sowan beach tourism village are not accommodated to the maximum. So that the existence of Sowan Beach has not been able to provide optimal benefits for the welfare and quality of life of the people of Bogorejo Village, Tuban, East Java.